Employee Voice in the Global North Insights from Europe, North America and Australia - Ajibade Adisa, Toyin; Mordi, Chima; Oruh, Emeka (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
XVII, 199 p. 1 illus.